2010
DOI: 10.1088/0953-4075/43/24/245504
|View full text |Cite
|
Sign up to set email alerts
|

Preparing superposition of squeezed coherent states under thermal reservoir

Abstract: We propose a scheme for engineering a superposition of squeezed coherent states into a lossy cavity and study its evolution under the influence of a thermal reservoir, providing analytical results for the Wigner function as well as for the Glauber–Sudarshan P function. To characterize this state, we study both the fidelity and the atomic inversion for several parameters, including some parameters taken out from recent experiments in cavity QED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…being D (α) = exp( α a † − α * a) and S (ξ) = exp 1 2 ξ * a 2 − ξ a †2 the displacement and squeezing operators, respectively. A scheme of generation of a superposition of squeezed coherent states of that type in a cavity has been presented in [25]. We are assuming the specific state in Eq.…”
Section: The System Modelmentioning
confidence: 99%
“…being D (α) = exp( α a † − α * a) and S (ξ) = exp 1 2 ξ * a 2 − ξ a †2 the displacement and squeezing operators, respectively. A scheme of generation of a superposition of squeezed coherent states of that type in a cavity has been presented in [25]. We are assuming the specific state in Eq.…”
Section: The System Modelmentioning
confidence: 99%
“…[24][25][26][27][28], where the authors showed how to prepare coherent states superposition (CSS) [26] and SCSS [24] into a lossy thermal cavity, studying its statistical dynamical properties [28], robustness against noise [25], and also providing a scheme to teleport SCSS from one lossy cavity to another [27]. Assuming the SCS or SCSS initially prepared into a lossy thermal cavity and sending a two-level atom to cross the cavity and to interact on-resonantly with either the SCS or SCSS, results (α 1 = α and α 2 = −α):…”
Section: The Modelmentioning
confidence: 99%
“…To this aim we consider, as in Ref. [24], initially a SCSS prepared in a singlemode of a high-Q cavity evolving under a thermal reservoir. After preparing the SCSS, a two-level atom, prepared in its excited state, is sent to interact resonantly with the lossy cavity-mode.…”
Section: Introductionmentioning
confidence: 99%